2020
DOI: 10.1021/acs.chemmater.0c03596
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic Iodide Adsorption Causes Anisotropic Growth of Copper Microplates

Abstract: Control over the shape of a metal nanostructure grants control over its properties, but the processes that cause solution-phase anisotropic growth of metal nanostructures are not fully understood. This article shows why the addition of a small amount (75–100 μM) of iodide ions to a Cu nanowire synthesis results in the formation of Cu microplates. Microplates are 100 nm thick and micronwide crystals that are thought to grow through atomic addition to {100} facets on their sides instead of the {111} facets on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 71 publications
4
50
0
Order By: Relevance
“…Previous studies of anisotropic growth of pentagonally twinned gold nanorods, copper nanowires, and copper microplates with single-crystal electrodes have also reported that the extent of anisotropic growth of the nanocrystal with planar defects is more than 10 times larger than can be accounted for from the ratios of the currents measured on (100) and (111) single-crystal electrodes. The difference in the extent of anisotropic growth observed for nanocrystals with planar defects and from measurements with single-crystal electrodes may be due to a similar effect as that observed in this work, i.e., that planar defects catalyze atomic deposition. Additional comparisons of the anisotropic growth of single-crystal seeds and seeds with planar defects under identical conditions, with accompanying single-crystal electrode measurements, may shed light on the extent to which planar defects catalyze atomic deposition for gold, copper, and palladium nanocrystals.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Previous studies of anisotropic growth of pentagonally twinned gold nanorods, copper nanowires, and copper microplates with single-crystal electrodes have also reported that the extent of anisotropic growth of the nanocrystal with planar defects is more than 10 times larger than can be accounted for from the ratios of the currents measured on (100) and (111) single-crystal electrodes. The difference in the extent of anisotropic growth observed for nanocrystals with planar defects and from measurements with single-crystal electrodes may be due to a similar effect as that observed in this work, i.e., that planar defects catalyze atomic deposition. Additional comparisons of the anisotropic growth of single-crystal seeds and seeds with planar defects under identical conditions, with accompanying single-crystal electrode measurements, may shed light on the extent to which planar defects catalyze atomic deposition for gold, copper, and palladium nanocrystals.…”
Section: Discussionsupporting
confidence: 73%
“…However, one can measure the current density ( j mp ) for either half-reaction at the mixed potential to determine the overall reaction rate. For spontaneous electrochemical reactions that are relatively slow, the j mp can be extracted from a Tafel plot of (log| j | vs E) obtained from the mixed reaction solution. The seed-mediated growth studied in this paper occurred too quickly for electrochemical analysis of the mixed reaction solution (the reaction is complete in 13 min), so we analyzed the two half-cell reactions separately. We compared reaction rates on Ag(100) and Ag(111) surfaces to measure how citrate affects the facet selectivity of the half-reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If facet-selective deposition cannot completely explain the growth of Cu nanowires with adsorbed Cl and HDA, we considered that surface diffusion could play a role. Our recent DFT study showed that Cl adsorption can reduce the surface energy of Cu(100), relative to Cu(111), and provide a thermodynamic driving force for the growth of {100}-faceted Cu nanostructures, such as nanowires. Herein, we show how this thermodynamic driving force is manifested kinetically, in faster Cu-atom surface diffusion on Cl-covered Cu(100) than on Cl-covered Cu(111). Below, we show how surface diffusion could play a key role in the growth of Cu nanowires.…”
Section: Introductionmentioning
confidence: 80%